Loitoktok One Health laboratory: A beacon of hope for livestock, community, and research - International Livestock Research Institute (International Livestock Research Institute, 2025)
The One Health Laboratory in Oloitoktok sub-County is managed in collaboration with the County Government of Kajiado. Interviews with members of the community, the local veterinary services and ILRI staff involved in operating and funding the lab show its importance and value.